Glutamate-based Therapies for Psychiatric Disorders - Skolnick, Phil.; Skolnick, Phil. (Milestones in Drug Therapy,, 2010)
Both metabotropic and ionotropic glutamate receptors present attractive “druggable” targets in treating disorders of the central nervous system. There has been a dramatic shift in the focus of glutamate-based therapies away from neurologic disorders such as stroke and traumatic brain injury to the treatment of psychiatric disorders. This “Milestones in Drug Therapy” volume offers a unique, contemporary overview of preclinical and clinical evidence that modulating glutamatergic tone is an effective means of treating psychiatric disorders ranging from depression and anxiety to schizophrenia and drug abuse. The ability to treat diseases such as depression and schizophrenia through multiple, glutamate-based mechanisms offers a unique therapeutic opportunity, as described in this book.